Exploring the Relationship Between Corporate Social Responsibility, Trust, Corporate Reputation, and Brand Equity - Zhao, Yan; Abbas, Manzir; Samma, Madeeha; Ozkut, Tarik; Munir, Mubbasher; Rasool, Samma Faiz (Frontiers in Psychology, 2021)
This study aims to explore the influence of corporate social responsibility (CSR) on corporate reputation (CR) and brand equity (BE). Building on the resource-based theory of the firm, this study proposes a theoretical framework. In this framework, corporate social responsibility is theorized to strengthen corporate reputation and brand equity, directly and indirectly, through consumer trust. Data were collected from the consumers of the banking sector in the vicinity of Lahore, Pakistan. To estimate the proposed relationships in the conceptual model, we use structural equation modelling through Smart PLS 3.2. The outcomes of this study confirm that corporate social responsibility significantly impacts corporate reputation and brand equity. It is also demonstrated that trust positively and significantly mediates in the relationship between corporate social responsibility, corporate reputation, and brand equity. Results of the present study have several implications for the senior management, marketing expert, administrators, and policymakers. This study expresses how corporate social responsibility boosts brand equity and corporate reputation. Moreover, this study also indicates that trust is an important factor that enhances brand equity and corporate reputation.